Long-Term Follow-Up of Children with Inflammatory Bowel Disease: Evaluation of 53 Cases - Ömer Faruk Beşer; Tufan Kutlu; Fügen Çullu Çokuğraş (Güncel Pediatri)
Introduction: In this study it was aimed to determine the long-term demographic, clinical and laboratory characteristics, together with the responses to therapy, in children diagnosed with inflammatory bowel disease (IBD). Materials and Methods: Fifty-three cases, aged 0 to 18 years, followedup with the diagnosis of IBD were included in this study. The study grouponsisted of patients diagnosed as IBD according to clinical, serologic, endoscopic and histopathological criteria. Dates of birth, esophagogastroduodenoscopy/colonoscopy findings, laboratory results at the time of diagnosis and during follow-up, complaints and their durations, treatments received presently and previously and comorbid diseases were documented. Patients’ heights, weights and Z scores at the time of diagnosis and following treatment were documented, calculated and compared. Family history of IBD and autoimmune disorders were questioned and recorded together with physical examination findings.Results: Among our cases, 18 were followed up with the diagnosis of Crohn’s disease (CD) and 35 had the diagnosis of ulcerative colitis (UC). Male to female ratio was 3.5/1 in CD and 1.33/1 in UC. Ten cases (18.9%) had the history of having a relative with IBD in their families. Mean age for start of complaints of this group was statistically significantly lower than the group having no family history of IBD (p=0.042). Twenty of the cases (37.8%) had history of consanguinity between parents. Mean age for start of complaints of this group, whose parents were consanguine, was statistically significantly lower than the group with non-related parents (p=0.025). Weight-for-age Z-score was below -2 in 18.9% of cases and seven of them were diagnosed with CD. Height-forage Z-score was below -2 in 17% of cases and nine of them were also followed-up with the diagnosis of CD. The white blood cell count, erythrocyte sedimentation rate and C-reactive protein value at the time of diagnosis were statistically significantly decreased following treatment (p<0.001). Resistance to first-line treatment was 14.3% in UC and 33.3% in CD. Conclusions: We determined an earlier onset of IBD in cases having consanguineous parents or another relative with IBD, considering that genetic mutations may play a role in etiology of the disease. Reversal of growth retardation, physical examination findings and laboratory parameters by treatment reveals the value of active patient follow-up in IBD.